Literatur Review Obat Tradisional Dalam Mengatasi Keputihan - Saputri, Resti Dona; Fauzia, Erlina (NERSMID : Jurnal Keperawatan dan Kebidanan, 2023)
Vaginal discharge is one of the problems that often occurs in women in the vaginal area characterized by non-blood discharge from the vagina. Alternative treatments for vaginal discharge can be done by utilizing traditional medicinal plants. This literature review aims to summarize some traditional medicines in Indonesia that can be used in overcoming vaginal discharge. This literature search using a database from Google Scoolar from 2019 to 2024 obtained as many as 3010 journals related to traditional whitish medicine. The results of data analysis in this literature are presented in the form of tables and narratives. Based on the results of the study, it was found that there are several traditional medicinal plants that can overcome the problem of vaginal discharge including green betel leaves, red betel leaves, soursop leaves, red rose tea, hobo onions, basil leaves, turmeric, turmeric acid and coriander seeds. This traditional plant is more easily available, costs less than modern medicine, can be made by yourself and is practical so that traditional medicinal plants are recommended for women who experience vaginal discharge problems.